DEVELOPING ENGLISH LEARNING MATERIALS FOR GRADE X STUDENTS OF BEAUTY STUDY PROGRAM AT SMK NEGERI 5 PONTIANAK - Dizza, Primatasha Desvira; Sutapa, Yohanes Gatot; Supardi, Iwan (English Language Education Study Program, 2021)
This research was aimed to develop supplementary material for the first semester of Tenth grade students of Beauty Study Program at SMK Negeri 5 Pontianak. The procedure of this research was ADDIE, it was conducted through the following steps: analyzing the needs, designing the framework, developing the materials, try out the materials, and evaluating the materials. The needs analysis reveals the students of Beauty Study Program needed a particular materials supporting their knowledge about communicating with costumers at a salon. The supplementary materials provided 4 units. They are Dear costumers, may I have your name?; Congrats for your new position!; I would like to dye my hair; and keep your attention, please. Based on the implementation, the students were more enthusiastic in learning English. All of the students follow the teaching and learning process actively since the first time. Based on the expert validation this product considered as valid to be used by the students, as well as the feedback from the participant prove that this supplementary material appropriate to be used. In conclusion, the English learning materials for the grade X students of Beauty Study Program at SMK Negeri 5 Pontianak has successfully developed and could be used as a supplementary material. First, the researcher suggests that the need analysis sheets should be applied in order to meet specific needs of the learners. Second, the prototype is needed to help the researcher develop the supplementary material based on the criteria. Third, evaluation by expert perception is needed to find out the feasibility of supplementary material and feedback is needed in order to make the developing material be more excellent.